Bob Jahn, Co-Founder of SSE - Sturrock, Peter (Journal of Scientific Exploration, 2018)
Thank you for the Bob Jahn tributes published in the Spring issue of the Journal. Bob was a remarkable individual and a tremendous asset to Society for Scientific Exploration. He was a wise councilor and an efficient and effective officer, who was a mainstay of the Society over the last three decades of our history. Bob did more than anyone to help SSE grow into the sound, effective, and productive organization it is today. Bob also exemplified what is best in science. He was open-minded, he paid attention to the evidence, and he thought long and hard about theoretical implications and interpretations. Are not all scientists open-minded? Regrettably, the answer is no. Scientists are also human beings, and the human tendency is to believe what one wants to believe. When faced with a new idea, most scientists will look for—and manage to find—a reason to discount it. Bob was not like that. He would refrain from giving an off-the-cuff response, he would ask a few probing questions, and then he would go away and think about it. When faced with the challenge of understanding the branch of parapsychology that deals with mind–matter interaction, he wisely decided to first acquire the best set of data that he could. This led to a sequence of very carefully planned experiments that extended over decades, and which now comprise one of the most reliable and informative datasets in the field. After many years of innovative experimental work, Bob was ready to start thinking about its theoretical interpretation. These thoughts evolved over time, leading eventually to the sophisticated concepts embodied in his M5 model (for Modular Model of Mind–Matter Manifestations).